An Overview of the Migration of Micro Religions Pertaining to India - Amal Sarkar (Jai Maa Saraswati Gyandayini An International Multidisciplinary e-Journal, 2016)
INDIA is the only country where not only many religions like Hinduism, Buddhism, Jainism, Sikhism have originated but also, it is the home of a large number of other religions like Islam, Christianity, Zoroastrianism, Judaism and Baha’i. With respect to the number of followers of various religions in India, they can be classified as Major, Minor and Micro religions. Hinduism and Islam are the major religions of the country (each followed by more than 10% of the population). Christianity, Buddhism, Jainism and Sikhism are followed by considerable population of the country (more than 0.4% and less than 3%); hence they can be termed as minor religions. Rest religions which have a share of less than 0.4% of the Indian population and can be termed as micro religions. The article focuses on the spatial and temporal dimensions of these micro religions which have been traced not only with respect to migration but also their language and culture. The micro religions which have originated in the country and have not practiced any sought of migration, have not been considered. Most of these micro religions immigrated to India from Persia, in order to save from persecution of the followers of these religions in their homeland.